EFFICIENCY OF COCOA SHELL FLOUR (THEOBROMA CACAO) IN THE REMOVAL OF TURBIDITY FROM DOMESTIC WASTEWATER - Pinchi Del Aguila, Mark Gabriel (2022)
The objective of the article was to analyze the efficiency of cocoa (Theobroma cacao) shell flour in removing turbidity from domestic wastewater. The coagulant doses were 600, 800, and 1000 mg/L, with a fast speed of 180 RPM for one minute, a slow speed (40 and 60 RPM) for 15 minutes, and a settling time of 15 minutes. The volume of each jar was 1 L. A p-value of 0.001 was found for the slow speed factor; that is, there is a significant difference in turbidity for the two slow speed values. For the flocculant concentration factor, the p-value was 0.737; that is, there is no significant difference in turbidity for the four values of flocculant concentration. Likewise, the p-value for the (slow speed * concentration interaction) was 0.737; that is, it was not significant. It is concluded that the use of natural flocculants is a sustainable alternative for the removal of turbidity from domestic wastewater